Activator-assisted pyrolysis of polypropylene. (1st November 2019) - Park, Ki-Bum; Jeong, Yong-Seong; Kim, Joo-Sik
Highlights: A novel activator–assisted pyrolysis of polypropylene was successfully conducted. The activator–assisted pyrolysis process showed a new degradation pathway. Pyrolysis oil contained mainly aromatic hydrocarbons (max. 92 wt%). Pyrolysis gas was mainly composed of olefins, H2 and CH4 . Activated PP molecules had 10 kJ/mol lower activation energy than unactivated ones. Abstract: One of the most promising ways to recycle plastic is pyrolysis. Valuable fuels and chemicals can be obtained by pyrolysis of waste plastic. In this study, pyrolysis of polypropylene was conducted using a novel continuous two-stage process equipped with auger and fluidized bed reactors connected in series. The auger reactor played an important role as an activator to elevate the vibrational states of molecules fed into the fluidized bed reactor. Hence, the two-stage pyrolysis conducted herein was called activator-assisted pyrolysis. In this study, the effects of the temperatures of the auger reactor (or activator) and bubbling and freeboard zones of the fluidized bed reactor, the type of the fluidizing medium (product gas and N2 ), and the residence time of pyrolysis vapor on the product distribution and composition were investigated. In the experiments, the activator facilitated decomposition of polypropylene molecules, resulting in a high yield of the product gases (81 wt%) consisting mainly of H2 and CH4 . The maximum olefin (ethene, propene, 1, 3-butadiene, and butenes) yield was 52 wt%. The pyrolysis oil mainly consisted of aromatics (up to 92 wt%), particularly mono-aromatics. The activation energies of the activated and unactivated molecules were calculated using the Friedman and Flynn–Ozawa–Wall methods. The activation energy of the activated molecules was approximately 17 kJ/mol lower than that of unactivated molecules. Hence, it was clear that the degradation mechanism of polypropylene was different when activator-assisted pyrolysis was applied. The new activator-assisted pyrolysis proposed in the current work could be helpful to produce valuable chemicals from the pyrolysis of polyolefin waste.